A horizon scan of global conservation issues for 2014 - Sutherland, William J.; Aveling, Rosalind; Brooks, Thomas M.; Clout, Mick; Dicks, Lynn V.; Fellman, Liz; Fleishman, Erica; Gibbons, David W.; Keim, Brandon; Lickorish, Fiona; Monk, Kathryn A.; Mortimer, Diana; et al. (Trends in ecology & evolution (Amsterdam), 2014)
•This is the fifth in our annual series of horizon scans published in TREE.•We identify 15 issues that we considered insufficiently known by the conservation community.•These cover a wide range of issues. Four relate to climate change, two to invasives and two to disease spread.•This exercise has been influential in the past. This paper presents the output of our fifth annual horizon-scanning exercise, which aims to identify topics that increasingly may affect conservation of biological diversity, but have yet to be widely considered. A team of professional horizon scanners, researchers, practitioners, and a journalist identified 15 topics which were identified via an iterative, Delphi-like process. The 15 topics include a carbon market induced financial crash, rapid geographic expansion of macroalgal cultivation, genetic control of invasive species, probiotic therapy for amphibians, and an emerging snake fungal disease.